Improving Speaking Skills in English through Advertising Language - M Firas Al Farisi; Godefridus Bali Geroda (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
The entry of social life, human communicate with Language, there are many Languages made by agreement from the community of people, in the era of industrial technology, Advertising Language is one of the Languages that use ability to speak, The ability to handle conversations in real-time through advertising skills. The purpose of this study is to investigate features of advertising Language as a method of learning speaking English. This paper utilized Observation and Interview to gather the data. There are take Primary and Secondary data. The results of this study show the used of Advertising Language on the video assignment by the students are containing the features of advertising Language, and the result of the interview session that student helpful with the advertising Language to speech and supporting that can improve speaking English skills. Advertising Language have basic representations of perception that are interesting. Therefore, the researcher found that the function of the advertising Language features used had helped the subject speak both consciously and unconsciously, as a result of observations and in-depth interviews, the students have their own narrative that they fully supported the advertising Language itself use as a method of improving speaking English skills on the future.